Stability Analysis and Verification of Real-Time Hybrid Simulation Using a Shake Table for Building Mass Damper Systems - Chen, Pei-Ching; Dong, Meng-Wei; Chen, Po-Chang; Nakata, Narutoshi (Frontiers in Built Environment, 2020)
The building mass damper (BMD) system, which incorporates the concept of a tuned mass damper into a mid-story isolation system, has been demonstrated as an effective system for suppressing structural vibration due to earthquakes. The BMD system separates a building into a substructure, a control layer and a superstructure. By applying well-design parameters, the seismic responses of the superstructure and substructure of a building can be mitigated simultaneously. However, merely limited design parameters have been verified by shaking table testing because it is difficult to construct several sets of specimens with limited research funding. Therefore, real-time hybrid simulation (RTHS) may become an alternative to conduct parametric studies of the BMD system efficiently and economically. In this study, the BMD system is separated into a numerical substructure and an experimental substructure. The experimental substructure includes the control layer and the superstructure of the BMD system installed on a seismic shake table while the substructure is numerically simulated. Then, substructuring method of the BMD system is derived and the stability analysis considering the dynamics of the shake table is performed to realize the potential feasibility of RTHS for BMD systems. The stability margin is represented as an allowable mass ratio of the experimental substructure to the entire BMD system. Finally, RTHS of a simplified BMD system has been conducted to verify the stability margin in the laboratory. Phase-lead compensation and force correction are applied to RTHS in order to improve the accuracy of RTHS for the simplified BMD system.